Formulation, characterization and invitro permeation/penetration of a-Arbutin creams and hydrogel / Nurul Fatin Fakhira Mohd Padli - Mohd Padli, Nurul Fatin Fakhira (2020)
a-Arbutin is a skin whitening active which is highly hydrophilic and difficult to permeate into hydrophobic skin barrier. Nowadays, cosmetic consumers are mainly focused on the multi-sensory experience of a cosmetic product. However, a cosmetic product with good sensory feeling upon application is not sufficient without ensuring the effectiveness of a-arbutin to be permeated well into the epidermis. In this study, a-arbutin creams and hydrogel were prepared to determine the influence of emulsifying thickener, polymer and natural oils on texture and permeation of a-arbutin. Prior to creams and hydrogel formulation, different types of polymer solution such as Carbopol® Ultrez-30, Aquagel 35C, Aquagel 45, Sepigel 305™ and SepiMax Zen™ were screened by evaluating the texture of formulations and diffusion profile of a-arbutin. Aquagel 35C was selected to be used in the optimized formulation because it offered good emulsification and aesthetically appealing in spite of moderate diffusion of a-arbutin. Then, a-arbutin creams and hydrogel were formulated and optimized by using thickeners (Ceteareth-20/cetearyl alcohol or Olivem® 1000 or Olivem® 2020) and natural oils (olive oil or palm kernel oil). Subsequently, the physicochemical properties of formulations were characterized. The result showed that all of the formulations exhibited good texture and stability within shelf-life of 6 months as well as possessed shear-thinning properties which is an ideal characteristic in cosmetic application. Then, each creams and hydrogel were subjected to Franz Diffusion Cell by using a cellulose acetate membrane and rat skin at 37°C for 6 hours. Then, the sample was analyzed by using High-Performance Liquid Chromatography (HPLC) to determine the amount, flux and diffusion coefficient of a-arbutin. Invitro transmembrane diffusion study by using cellulose acetate membrane showed that hydrogel has the highest cumulative amount of 1490.7 ± 1.06 /ig of a-arbutin. Then, a cream containing palm kernel oil and Olivem® 2020 offered higher diffusion of a-arbutin (1263.7 ± 23 A fig) than other creams. In contrast, the invitro rat skin permeation and penetration study revealed that formulation containing palm kernel oil and Cetearyl alcohol/Ceteareth-20 has better permeation than Olivem® 1000 and Olivem® 2020. In conclusion, the study suggested that hydrogel and creams containing palm kernel oil can enhance the permeation of aarbutin than creams with olive oil, meanwhile, Olivem® 2020 offered better physical appearance and sensory feeling hence they are recommended to be used in cosmetic preparation.